Investigation of layer thickness effect on the performance of low-cost and commercial fused deposition modelling printers - Syamsuzzaman, M.; Mardi, N.A.; Fadzil, M.; Farazila, Y. (Maney Publishing, 2014)
Rapid prototyping is one of the common technologies in additive manufacturing. The layer-by-layer mechanism of rapid prototyping allows this technology to rapidly create and print complex geometries from three-dimensional models of any objects. Fused deposition modelling is one of the common processes in rapid prototyping, and its maturity has given birth to full-scale, commercial fused deposition modelling machines, as well as low-cost, fused deposition modelling machines, which are also referred to as three-dimensional printers. This work compares the effect of layer thickness during printing on the tensile and compressive strengths of samples, for commercial and low-cost fused deposition modelling machines. Standard samples based on ASTM D638 and ASTM D695 were prepared for the tensile and compressive tests, with layer thicknesses of 0.3302 and 0.2540 mm, using acrylonitrile butadiene styrene as the printing material. From the tensile tests, specimens prepared using low-cost fused deposition modelling managed to obtain only 41.87 and 54.69% of the ultimate tensile strength of specimens prepared using commercial fused deposition modelling, for layer thicknesses of 0.3302 and 0.2540 mm. Meanwhile, from the compressive tests, specimens prepared using low-cost fused deposition modelling managed to obtain only 75.55 and 73.79% of the ultimate compressive strength of specimens prepared using commercial fused deposition modelling, for the same layer thicknesses. Ultimately, low-cost fused deposition modelling still needs more improvement in order to give better results, compared to the currently available commercial-grade fused deposition modelling printers.